2013
DOI: 10.1186/1471-2474-14-45
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic evaluation of the abductor hallucis muscle in hallux valgus: a cross-sectional observational study

Abstract: BackgroundThe aim of the study was to investigate the abductor hallucis muscle characteristics, defined as dorso-plantar (DP) thickness, medio-lateral (ML) width, and cross-sectional area (CSA) in relation to the severity of hallux valgus using musculoskeletal ultrasound. One hundred and two feet, mean (SD) age of 60.3 (20.54) years old, displaying varying severities of hallux valgus were stratified into four groups representing the four grades of the Manchester Scale (grade 0: no deformity, grade 1: mild defo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 43 publications
(59 reference statements)
4
53
4
Order By: Relevance
“…Decreased ankle plantarflexor strength is associated with difficulties in rising onto the toes [37], and toe plantarflexor weakness impairs the grasping function of the toes when performing weight-bearing activities, resulting in impaired balance and functional ability [3] and an increased risk of falls [4,38]. Atrophy and the associated reduced strength of the toe muscles may also play a role in the development of toe deformities, as a reduced thickness of intrinsic musculature has been identified in older people with hallux valgus and lesser toe deformities [39,40] on ultrasound images, and older people with toe deformities exhibit reduced toe plantarflexor strength compared to those without toe deformity [38,41]. …”
Section: Age-related Changes In Foot Strengthmentioning
confidence: 99%
“…Decreased ankle plantarflexor strength is associated with difficulties in rising onto the toes [37], and toe plantarflexor weakness impairs the grasping function of the toes when performing weight-bearing activities, resulting in impaired balance and functional ability [3] and an increased risk of falls [4,38]. Atrophy and the associated reduced strength of the toe muscles may also play a role in the development of toe deformities, as a reduced thickness of intrinsic musculature has been identified in older people with hallux valgus and lesser toe deformities [39,40] on ultrasound images, and older people with toe deformities exhibit reduced toe plantarflexor strength compared to those without toe deformity [38,41]. …”
Section: Age-related Changes In Foot Strengthmentioning
confidence: 99%
“…The extrinsic foot muscles primarily provide osteokinematic movements, 1,2 whereas the intrinsic foot muscles maintain the medial longitudinal arch, [3][4][5][6] control the degree and velocity of arch deformation, 7 and aid in postural control during stance and gait. [8][9][10][11] Several conditions, such as plantar fasciopathy, 1,3,6 hallux valgus, [12][13][14] and pes planus, 1,12,15,16 are associated with weakened or atrophied intrinsic foot muscles. Rehabilitation and strengthening of these muscles are used to treat these conditions, 1,2,17 and prophylactic exercises targeting the intrinsic foot muscles may aid in injury prevention.…”
mentioning
confidence: 99%
“…1 Another study also reported significant differences in MT and CSA of the AbdH between different severities of HV. 8 However, another study showed that regardless of the type of US machine, the intra-rater reliability for AbdH muscle measurements was excellent. 17 In addition, the previous study performed similarly with present study, US measurement of AbdH muscle for intra-and inter-rater reliability study was conducted with excellent reliability in asymptomatic subjects.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the spring gauge was replaced with other spring gauges 6 times, after measurements of 5 subjects, to avoid loss of spring elasticity due to fatigue with extensive use of the spring gauges. 16 Various studies have reported on MT measurements of the AbdH using US according to different ages 1 , different grades of HV severity 8 , and different measuring machines. 17 The previous study reported that increased patient age is related to greater reduction of MT and CSA of the AbdH on the side with HV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation